Ischemic preconditioning does not improve judo-specific performance but leads to better recovery in elite judo athletes - Ceylan, B.; Franchini, E. (Science & Sports, 2022)
Objectives Although there are numerous studies related to effect of ischemic preconditioning on performance, there is a lack of studies demonstrating the effect of ischemic preconditioning on sport specific performance and recovery. Thus, this study aimed to demonstrate the effects of ischemic preconditioning on judo-specific performance and recovery. Equipment and methods Ten men elite judo athletes (age = 20.0 years ± 2.2, judo experience = 9.6 years ± 1.9) voluntarily participated in this study. A controlled single-blinded crossover design was used to assess the effect of ischemic preconditioning on judo-specific performance and recovery. Athletes executed three test sessions including familiarization, ischemic preconditioning and control conditions. In each session, they executed the special judo fitness test. Heart rate was measured before, immediately after and 1, 3, 5 and 10 min, whereas blood lactate concentration was measured before and 3, 5, 10 min after the judo specific test. Oxygen saturation and blood pressure were monitored during ischemic preconditioning application. Results No difference was found concerning the oxygen saturation during the ischemic pre-conditioning (P > 0.05). Heart rate and lactate responses in control condition were higher compared to ischemic preconditioning condition (P < 0.01). Systolic blood pressure also differed across moments of measurement during judo specific test (P < 0.01). No effect of condition was found for number of throws and index during judo specific test. Ischemic preconditioning has no impact on judo specific performance, but resulted in lower heart rate and lactate concentration, further studies are warranted to investigate effect of ischemic preconditioning on recovery in judo athletes during a competition day or following judo-specific activities.